Effect of Green Lean Body Capsules on Body Weight, Lipid Profile, and Renal Physiology and Histology in Albino Rats - Al-Lami, Makarim Q. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Many anti-obesity medicines have been increased in recent years to solve the problem of obesity; among these medicines are Green Lean Body Capsules (GLBCs) which contain green plants and fruits extract.Objective: This study was designed to evaluate the effects of daily oral consumption of GLBCs on level of serum lipids, renal function tests, and the histological structure of the kidney in albino rats.Materials and Methods: Twenty adult albino male rats weighing 240-260 g were divided into 2 equal groups: control group and GLBCs-treated group. During the 4-weeks treatment, each rat in the GLBCs-treated group was orally administered with 20 mg/kg B.W. of GLBCs, while the control rats were orally administered with 0.1 ml D.W. Body weights were monitored at the beginning and at the end of the experimental period. Lipid profile [total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), very lowdensity lipoprotein cholesterol (VLDL-C) and low-density lipoprotein cholesterol (LDL-C)], renal function tests (blood urea and serum creatinine) ; in addition to the histological examination of the kidney wereevaluated in all the rats.Results: The results revealed that body weight gain was significantly (P